Main Street West Side Between 200 and 300 - Shipler Commercial Photographers; Shipler, Harry (Utah State Historical Society; Funded by a grant from the National Endowment for the Humanities, 1918)
Image shows a general view of the Hudson Bay Fur Company storefront, the Leyson Jewelry Company building, and adjacent businesses on Main Street. This image included in both the Shipler and the Classified photograph collections.